2015
DOI: 10.1002/2014gc005581
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic arc structure around Mount Rainier, WA, from the joint inversion of receiver functions and surface wave dispersion

Abstract: The deep magmatic processes in volcanic arcs are often poorly understood. We analyze the shear wave velocity (V S ) distribution in the crust and uppermost mantle below Mount Rainier, in the Cascades arc, resolving the main velocity contrasts based on converted phases within P coda via source normalization or receiver function (RF) analysis. To alleviate the trade-off between depth and velocity, we use long period phase velocities (25-100 s) obtained from earthquake surface waves, and at shorter period (7-21 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 65 publications
(112 reference statements)
1
22
0
Order By: Relevance
“…Figures h and i, c and 11d, and Figure S7), although relative Vs patterns are stable and the forearc is consistently slower than farther east. Most upper mantle Vs values are 4.2–4.5 km/s, similar to observations beneath Mount Rainier (Obrebski et al, ). The higher values, observed east of MSH and near Mount Adams, resemble typical regional (Shen & Ritzwoller, ) and global (Christensen & Mooney, ) upper‐mantle Vs .…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Figures h and i, c and 11d, and Figure S7), although relative Vs patterns are stable and the forearc is consistently slower than farther east. Most upper mantle Vs values are 4.2–4.5 km/s, similar to observations beneath Mount Rainier (Obrebski et al, ). The higher values, observed east of MSH and near Mount Adams, resemble typical regional (Shen & Ritzwoller, ) and global (Christensen & Mooney, ) upper‐mantle Vs .…”
Section: Resultssupporting
confidence: 85%
“…(b) The gradient model or Vs R for a smoothed Moho. The original starting model (dashed black) is a moving average of the Group 1 average Vs from Obrebski et al (). Solid black line is the resulting Vs R , referred to as the “gradient model.” Monte Carlo uncertainties shown in solid red, as 1‐σ (dark) and 2‐σ (light) uncertainties.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous active and passive-source seismic studies have observed weak or absent Moho arrivals at other locations within the Cascadia forearc region141618 (Fig. 1), including a reversal of the Moho velocity contrast in central Oregon13.…”
Section: Discussionmentioning
confidence: 77%
“…Locations of the major Quaternary volcanoes active are plotted as red triangles and the grey regions depict the distribution of volcanic vents7. Yellow boxes show where previous seismic experiments have observed a weak Moho arrival131418. The red shaded region denotes the location of the Southern Washington Cascades Conductor2829.…”
Section: Figurementioning
confidence: 99%